THE EFFICACY OF MUSCLE ENERGY TECHNIQUE IN INDIVIDUALS WITH MECHANICAL NECK PAIN: A SYSTEMATIC REVIEW - Made Hendra Satria Nugraha; Ni Komang Ayu Juni Antari; Ni Luh Putu Gita Karunia Saraswati (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2020)
Introduction: Mechanical neck pain is a condition that includes minor strain / sprain in the muscles, ligaments, or facet joint dysfunction. Objective: This systematic review is aimed to find out the effectiveness of the muscle energy technique in mechanical neck pain. Method: The systematic review access to journal databases such as: PubMed, PEDro, and the Cochrane Library. Results: Based on inclusion and exclusion criteria 5 articles were used in this systematic review. The application of the muscle energy techniques was applied ranging from 1 time to 4 weeks of intervention. From the 5 reviewed studies concluded that muscle energy technique was effective in improving neck motion and function in mechanical neck pain. Conclusion: Based on the results of systematic review it can be concluded that the application of MET improve neck movement through The International Classification of Functioning, Disability, and Health (ICF) criteria evaluated by pain score, pain threshold, range of motion, functional performance, and muscle thickness. The appropriate articles are still limited to 5 studies, but have good to strong qualities. In addition, the application of intervention does not have the same standard.